A ring of tricksters : animal tales from America, the West Indies, and Africa - Hamilton, Virginia, 1934-2002.; Moser, Barry (New York : Blue Sky Press, 1997)
Twelve trickster tales that show the migration of African culture to America via the West Indies.
Keywords: African Americans -- Folklore; Tricksters -- Juvenile literature; Tales -- Africa; Tales -- West Indies; Tales -- Southern States; Tricksters -- Folklore; Folklore -- Africa; Folklore -- West Indies; Folklore -- Southern States